Search for CP violation in the Dalitz-plot analysis of D±→K+K- π± - Rubin, P; Eisenstein, B; Karliner, I; Mehrabyan, S; Lowrey, N; Selen, M; White, E; Wiss, J; Mitchell, R; Shepherd, MR; Besson, D; Pedlar, T; et al. (2008)
We report on a search for CP asymmetry in the singly Cabibbo-suppressed decay D+→K+K-π+ using a data sample of 818pb-1 accumulated with the CLEO-c detector on the ψ(3770) resonance. A Dalitz-plot analysis is used to determine the amplitudes of the intermediate states. We find no evidence for CP violation either in specific two-body amplitudes or integrated over the entire phase space. The CP asymmetry in the latter case is measured to be (-0.03±0.84±0.29)%. © 2008 The American Physical Society.